Tower of the Palace of Science (Western Publishing & Novelty Company)
Said to be one of the finest examples of Spanish Renaissance architecture ni America. From the tower, which is 210 feet high, may be seen a magnificent panorama of the Exposition grounds, the bay, ocean, and mountains.